If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7h + -3) = 120 Reorder the terms: 2(-3 + 7h) = 120 (-3 * 2 + 7h * 2) = 120 (-6 + 14h) = 120 Solving -6 + 14h = 120 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 14h = 120 + 6 Combine like terms: -6 + 6 = 0 0 + 14h = 120 + 6 14h = 120 + 6 Combine like terms: 120 + 6 = 126 14h = 126 Divide each side by '14'. h = 9 Simplifying h = 9
| 4-4(x-3)=20 | | 8-5=11 | | -(1-x)=2(3x-1) | | 9y-6+y=-(y+5y) | | 7r+11r=725-7r | | 5(b+1)=5b+1 | | -25=7+4x | | 5(2x-31)+3=10x-155 | | 6(x-8)-3x=5(x-1)-1 | | 3+5-6+2x=-4(x-3)+7 | | -9(4x-2)=108-6x | | 4(2x+2)=7x+1 | | 6x+3x-x=96 | | 2c-11c+5=0 | | 2(m-3)=2(m-6) | | 5x^2-30x+100=0 | | 4(-5-x)=10-2x | | -.25x-9=.90 | | 8-h=-4 | | .28=.04(w-1.0) | | -4-6x=20 | | .28=.04(w-10) | | (3x^3)-(2x^2)= | | 0.4x-3.4=46 | | -.25-9=.90 | | 2x+11=3x+4 | | 3x^3-2x^2= | | -6m+69-9(m+1)=4m-(2m-2)-7m+6 | | 1170=68 | | (X^2+x-6)(x^2+x-2)+3= | | 0.50h-7=15 | | 9f+5(-8+3f)= |